Characteristic of Japanese traditional communication - Le, Thi Thu Hong (Vietnam National University, Hanoi, 2020)
Due to of Japan characteristic natural, social, cultural conditions, the communication of Japanese has special feature; Japanese are not open; Japanese ruling are very coureoxs in communication and they are interested in the relax of the counterpart. Today, Japan is a power nation in the world, but the Japanese always have the idea to maintain their traditions and the culture heritages of their ancestors